Pharmacokinetics, metabolism, and excretion of nefopam, a dual reuptake inhibitor in healthy male volunteers. (1st November 2016) - Sanga, Madhu; Banach, John; Ledvina, Aaron; Modi, Nishit B.; Mittur, Aravind
Abstract: 1. The disposition of nefopam, a serotonin–norepinephrine reuptake inhibitor, was characterized in eight healthy male volunteers following a single oral dose of 75 mg [ 14 C]-nefopam (100 μCi). Blood, urine, and feces were sampled for 168 h post-dose. 2. Mean (± SD) maximum blood and plasma radioactivity concentrations were 359 ± 34.2 and 638 ± 64.7 ngEq free base/g, respectively, at 2 h post-dose. Recovery of radioactive dose was complete (mean 92.6%); a mean of 79.3% and 13.4% of the dose was recovered in urine and feces, respectively. 3. Three main radioactive peaks were observed in plasma (metabolites M2 A-D, M61, and M63). Intact [ 14 C]-nefopam was less than 5% of the total radioactivity in plasma. In urine, the major metabolites were M63, M2 A-D, and M51 which accounted for 22.9%, 9.8%, and 8.1% of the dose, respectively. An unknown entity, M55, was the major metabolite in feces (4.6% of dose). Excretion of unchanged [ 14 C]-nefopam was minimal.